Teplizumab: a new glimmer of hope for type 1 diabetic patients - Garg, Preeti; Sangeeta Bhanwra; Rajiv Kumar (International Journal of Basic & Clinical Pharmacology, 2023)
Teplizumab is the first monoclonal antibody used to delay the onset of stage 3 type 1 diabetes mellitus (DM). It is a highly selective, a CD3-directed monoclonal antibody, given parenterally that was approved in November 2022, for delaying the onset of Stage 3 type 1 diabetes in adults and paediatric patients aged 8 years and older with stage 2 type 1 Diabetes. It binds to the immune cells that destroy the insulin producing pancreatic beta cells and inactivates them thereby leading to decreased rate of reduction in insulin production and subsequently delay in the onset of stage 3 type 1 diabetes.